Clinical characteristics indicating adenomyosis at the time of hysterectomy: a retrospective study in 291 patients - Ţăran, Florin-Andrei; Wallwiener, Markus; Krämer, Bernhard (Archives of gynecology and obstetrics, 2012)
PurposeTo better characterize adenomyosis as a disease entity.MethodsWe retrospectively reviewed the medical records of women undergoing hysterectomy with a histologic diagnosis of adenomyosis, adenomyosis and leiomyomas, and leiomyomas alone.ResultsThe study included 291 women: 38 with adenomyosis alone, 56 with adenomyosis and leiomyomas, and 197 with leiomyomas alone. In univariate analysis, women with adenomyosis were younger (p = 0.018) and had lower uterine weights (p < 0.001) and more disease-specific symptoms (p = 0.008). In multinomial logistic regression analysis, a lower uterine weight (OR 0.99, CI 95% 0.99-1.0), pelvic pain (OR 4.8, CI 95% 1.5-15.2), a history of smoking (OR 2.6, CI 95% 1.1-6.5) and at least one delivery (OR 4.3, CI 95% 1.5-12.3) were associated with a greater likelihood of having adenomyosis but not leiomyomas alone.ConclusionsWomen undergoing hysterectomy with adenomyosis alone have different clinical characteristics from women with adenomyosis and leiomyomas and from those with only leiomyomas.
Published online: 23 December 2011
Gesehen am 10.07.2018